2023
DOI: 10.1186/s12981-023-00538-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of depression and interpersonal support on adherence to antiretroviral therapy among people living with HIV

Abstract: Background Poor adherence and under-utilization of antiretroviral therapy (ART) services have been major setbacks to achieving 95-95-95 policy goals in Sub-Saharan Africa. Social support and mental health challenges may serve as barriers to accessing and adhering to ART but are under-studied in low-income countries. The purpose of this study was to examine the association of interpersonal support and depression scores with adherence to ART among persons living with HIV (PLWH) in the Volta regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Participants were excluded if they were seriously ill (defined as hospitalization) or had a mental impairment. More information on our study methods can be found elsewhere [25].…”
Section: Study Populationmentioning
confidence: 99%
“…Participants were excluded if they were seriously ill (defined as hospitalization) or had a mental impairment. More information on our study methods can be found elsewhere [25].…”
Section: Study Populationmentioning
confidence: 99%
“…Thus, a nal census of 181 participants was done for the study. Details of sample size and power calculations are published by the authors in Nutor et al (2023).…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…Studies on HIV status disclosure show disclosure outcomes can be complex and could result in isolation and diminished social support by partners if not well managed and supported (Kimberly et al, 1995). Indeed, a recent study in Ghana found that ART adherence rate was paradoxically higher among "status non-disclosed" group than "status disclosed" group (Nutor et al, 2023).…”
Section: Introductionmentioning
confidence: 98%
“…9 Within the context of social function, a crucial element is social support. 10 Furthermore, social support is associated with many health outcomes, such as ART adherence, 11 viral load suppression, 12 and anxiety and depression. 13 However, due to widely held misconceptions and stereotypes surrounding HIV, PLWH may encounter social discrimination and stigmatization, leading to a loss of social support and feelings of isolation.…”
Section: Introductionmentioning
confidence: 99%